(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
The translation of science fiction is a demanding yet intellectually stimulating task that goes beyond the simple transfer of words from one language to another. Due to the genre’s imaginative nature, translators are often required to deal with invented terminology, complex scientific concepts, and unfamiliar cultural references. This article examines practical and research-based translation methods and strategies that can be effectively applied in science fiction texts.